Genomic determinants in advanced endometrial cancer patients with sustained response to hormonal therapy- case series and review of literature - Chukkalore, Divya; Rajavel, Anisha; Asti, Divya; Dhar, Meekoo (Frontiers in Oncology, 2023)
The incidence of endometrial cancer is increasing, however treatment options for advanced disease are limited. Hormonal therapy has demonstrated positive outcomes for Stage IV EC. Next generation sequencing (NGS) has increased our understanding of molecular mechanisms driving EC. In this case series, we selected six patients at our institution with Stage IV, hormone receptor positive, endometrial cancer currently being treated with hormonal therapy. All patients achieved SD for at least ≥ 1.5 years. We studied NGS data on all six patients to assess for any common genomic marker which could predict the SD of at least 1.5 years achieved in this group. Institutional Review Board (IRB) approval was obtained from Staten Island University Hospital and Northwell Health, New York. PTEN, PIK3CA, PIK3R1, and ARID1A mutations were found in 83%, 67% 50%, and 67% of patients respectively. TP53 and FGFR2 were both found in 50% of patients. All patients were positive for estrogen and/or progesterone receptor (ER+ and/or PR+). We did not find any one common mutation that could have predicted the observed response (or SD of ≥1.5 years) to hormone therapy. However, our data reflects the prevalence of various mutations reported in literature: (1) Hormone Receptor status is a positive prognostic indicator (2) PTEN/PIK3CA mutations can occur concurrently in EC (3) ARID1A coexists with PTEN (4) FGFR and PTEN pathways may be interlinked. We suggest NGS be employed frequently in patients with endometrial cancer to identify targetable mutations. Additional larger studies are needed to characterize the interplay between mutations.